2011
DOI: 10.1007/s11089-011-0410-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Level of Pastors’ Risk of Termination/Exit from the Church

Abstract: This study conducts an exploratory factor analysis on Wickman's (2004) Pastors at Risk Inventory that measures the likelihood of whether clergy may face forced or unforced resignation. An online survey was administered to 285 evangelical pastors containing 42 Likerttype items developed from 20 years of qualitative practitioner ministry among clergy. The two factors identified-vision conflict and compassion fatigue-are discussed in relation to the extant literature and in their unique function with clergy. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
(18 reference statements)
0
18
0
Order By: Relevance
“…In addition, Spencer, Winston, and Bocarnea (2012) researched how compassion fatigue contributes to a high risk of pastoral termination/exit from the church. Pooler (2011) further explained how pastors create additional vulnerability to fatigue and burnout by striving to fulfill their perception of an ideal pastor:…”
Section: Pastors and Burnoutmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, Spencer, Winston, and Bocarnea (2012) researched how compassion fatigue contributes to a high risk of pastoral termination/exit from the church. Pooler (2011) further explained how pastors create additional vulnerability to fatigue and burnout by striving to fulfill their perception of an ideal pastor:…”
Section: Pastors and Burnoutmentioning
confidence: 99%
“…For example, pastors must support their parishioners with their personal problems such as death of loved ones, marital trouble and divorce, illness, loss of home, and loss of work. These heavy burdens are consistently carried by pastors on behalf of their peoplewith no respite (Spencer et al, 2012). In fact, most pastors are expected to care for their congregation like a shepherd would care for their flock.…”
Section: Pastors and Burnoutmentioning
confidence: 99%
See 2 more Smart Citations
“…A common and reoccurring factor according to earlier studies, is the experienced high levels of pastoral role stress. Research in the USA conducted by Spencer, Winston, & Bocarnea (2012) found that two factors stood out; vision conflict and compassion fatigue. Spencer, (2010) who discovered vision conflict, defines this role stressor as "the disparity between a minister's positive anticipation regarding ministry involvement and the actual experience itself.…”
Section: Introductionmentioning
confidence: 99%